2013
DOI: 10.1002/ca.22126
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the communicating branches of cords of the brachial plexus and their clinical implications

Abstract: The aim of this study was to investigate the occurrence and patterns of the communicating branches of cords of the brachial plexus (BPs). This study was performed with 50 fixed adult cadavers (all 100 sides). The BPs were exposed, the presence of the communicating branches of BPs were determined, measured, and photographed. The communicating branches were identified in 27 sides of the BPs. According to enthesis, the communicating branches between the medial and lateral cords (25 sides) were divided into five t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Sirico et al reported a 20% prevalence of musculocutaneous nerve variations in their meta‐analysis of 4124 plexuses (Sirico et al, 2019), aligning with our findings, which indicate these variations are not exceptionally common. Benes et al noted that variations in communicating branches are often overlooked in classifications of brachial plexus anomalies (Benes, Kachlik, Belbl, Kunc, et al, 2021, n = 3055 limbs), yet Song et al reported these as the most frequent in a study of 100 adults (Song et al, 2008), mirroring our observations. These anatomical variations, particularly in communicating branches, can significantly affect innervation and lead to clinical challenges such as altered sensory and motor functions or incomplete anesthesia in axillary blocks (Claassen et al, 2016; Orebaugh & Williams, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sirico et al reported a 20% prevalence of musculocutaneous nerve variations in their meta‐analysis of 4124 plexuses (Sirico et al, 2019), aligning with our findings, which indicate these variations are not exceptionally common. Benes et al noted that variations in communicating branches are often overlooked in classifications of brachial plexus anomalies (Benes, Kachlik, Belbl, Kunc, et al, 2021, n = 3055 limbs), yet Song et al reported these as the most frequent in a study of 100 adults (Song et al, 2008), mirroring our observations. These anatomical variations, particularly in communicating branches, can significantly affect innervation and lead to clinical challenges such as altered sensory and motor functions or incomplete anesthesia in axillary blocks (Claassen et al, 2016; Orebaugh & Williams, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…These anatomical variations, particularly in communicating branches, can significantly affect innervation and lead to clinical challenges such as altered sensory and motor functions or incomplete anesthesia in axillary blocks (Claassen et al, 2016; Orebaugh & Williams, 2009). It's critical for medical education to address these variations due to their potential clinical implications, emphasizing the necessity for awareness in diagnostic and therapeutic contexts (Song et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These connections with myelinated fibers are formed between dorsal rootlets and the spinal level below or above. There are many anastomoses between the BP cords and the path of the different terminal nerves and this highlights the absolute nervous continuum; in addition, branches of the cervical plexus involve the cutaneous area of the thoracic outlet such as the supraclavicular nerve [19]. We can find several nerves before branching into terminal branches.…”
Section: Review Thoracic Outlet: Cervical Plexus and Sympathetic Cervmentioning
confidence: 99%